ASPECTOS DO SUBLIME EM UMA CARTA DE GONÇALVES DIAS SOBRE A AMAZÔNIA - Nunes, Marcos Machado (Organon, 2012)
the text proposes a reading of a 1861 letter on the Amazon by Antonio Gonçalves Dias, making use of the aesthetical category of the sublime. This reading examines the letter in the context of the transculturation of the poetics of the sublime during the Brazilian Romantic period, following the general hypothesis that this cultural process presents connections with a rhetoric of nation-building identity.